IX Plan Mid Term Appraisal - Planning Commission (Planning Commission)
The first 3 years of the Five Year Plan are now almost over. The implementation of the 4th year of the 9th Plan will commence shortly. This period has seen many areas of success in our plan programmes where there have been significant achievements. There are a few areas where our achievements have fallen short of our goals. We had kept certain priorities before us when we embarked upon the 9th Five Year Plan. In the light of the developments in the first 3 years, the perception of our relative needs have also undergone some change.
Mid Term Appraisal for the Ninth Plan